KOMPETENSI PROFESIONALISME GURU - Dewi Wulandari (LPPM STAI La Tansa Mashiro, 2021)
A professional teacher must master four competencies,namely: 1. Pedagogic competence is the teacher's ability tomanage student learning. 2. Professional Competence. Thatis the ability of teachers to keep up with the latestdevelopments in science so that the development of science isalways dynamic. 3. Social competence will be seen whether ateacher can work together with the community and otherstudents and teachers. 4. Personality Competence. Thesecompetencies are related to the teacher's personality.Teachers must have noble qualities that can be role modelsfor their studentsSeorang guru yang profesional harus menguasai empatkompetensi, yaitu: 1. Kompetensi pedagogik adalahkemampuan guru mengelola pembelajaran siswa. 2.Kompetensi Profesional. Yaitu kemampuan guru untukmengikuti perkembangan ilmu pengetahuan terkini agarperkembangan ilmu selalu dinamis. 3. Kompetensi sosialakan terlihat apakah seorang guru dapat bekerja sama denganmasyarakat dan siswa serta guru lainnya. 4. KompetensiKepribadian. Kompetensi tersebut berkaitan dengankepribadian guru. Guru harus memiliki sifat luhur yang dapatmenjadi teladan bagi murid-muridnyaKata kunci : kompetensi, profesonalisme guru